Interactive Digital Media PanPinRu as an Effort to Increase Interest in Learning Students in Linear Equations of One Variable - Ani Afifah; Dewi Ainiyah; Sabeeha Hamzah Dehham (Delta-Phi: Jurnal Pendidikan Matematika, 2024)
This study aims to evaluate the effectiveness of interactive digital-based PanPinRu (Segment Moving Board) media in increasing the learning interest of class VII A students at SMP Darul Ulum 5 Grati on One Variable Linear Equations. The research method used is Design-Based Research, which emphasizes the iterative process of media development and implementation through collaboration between researchers, teachers, and students in a real classroom environment. PanPinRu media was developed as an interactive digital application that allows students to manipulate variables and constants virtually. It is equipped with automatic feedback features and game-based challenges (gamification). Data were collected through observations, learning interest questionnaires, interviews, and learning outcome tests, then analyzed qualitatively and quantitatively. The results showed that integrating interactive digital-based PanPinRu media significantly increased students' learning interest, with an average student response score of 65.57 (increased category) and an average student learning outcome of 84.74, which exceeded the Learning Objective Achievement Criteria. This finding confirms that interactive technology in mathematics learning media can be an innovative solution to improve student motivation and learning outcomes in the One Variable Linear Equation material